Investigation of Student Satisfaction with the Implementation of Learning Models in the Midst of a Pandemic Condition - Azizah, Humairoh; Nurnadia, Nurnadia; Dewi, Putri Selpiya (International Journal of Education and Teaching Zone, 2022)
This study aims to determine students' perceptions of the physics learning model applied by teachers in one of the high schools in Jambi City. The subjects in this study were SMA 9 Jambi City with a total sample of 15 students from classes XI and XII IPA. To find out students' perceptions of the physics learning model applied by the teacher, students were given an online questionnaire. Then the results of the student questionnaire answers were analyzed descriptively. From the results of the analysis, it can be concluded that students' perceptions of physics lessons are positive, especially in the midst of the Pandemic condition